Pengaruh Pemberian Madu Terhadap Pengeluaran Kolostrum Pada Ibu Post Partum Primipara Di RSU Asy Syifa' Sambi Kabupaten Boyolali - Anin Ari Wengi; Yuyun Triani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Colostrum is the type of breast milk that is richest in protein and provides extra protection against germs that attack the baby's digestive tract. Colostrum is the first immunization that babies receive which contains up to 17 times more anti-infective substances than other breast milk. How to stimulate colostrum production can be done with maternal nutrition. Giving honey to mothers is beneficial because honey contains nutrients (energy, carbohydrates, protein) which function as energy for the posterior pituitary to produce the hormones oxytocin and prolactin. Research Objective: To determine the effect of giving honey on colostrum production in primiparous postpartum mothers at Asy Syifa' Sambi General Hospital, Boyolali Regency. Research Method: Pre-experimental research type with posttest only with control group design. The population of this study was all post patum primiparous mothers on day 1 from 5 May 2023 to 28 June 2023 at RSU Asy Syifa' Sambi, Boyolali Regency, totaling 39 respondents. The sampling technique used consecutive sampling technique, the sample in this study was 16 respondents per group. The data analysis technique used is the Mann Whitney test. Research Results: The time to expel colostrum in primiparous postpartum mothers who were not given honey at Asy Syifa' Sambi General Hospital, Boyolali Regency had a mean of 3.31 hours, a median of 3.25 hours. The time to expel colostrum in primiparous postpartum mothers who were given honey had a mean of 0, 84 hour median 0.75 hours and standard deviation 0.25. There is an effect of giving honey on colostrum production in primiparous post partum mothers (0.000<0.05). Conclusion: There is an effect of giving honey on colostrum production in primiparous post partum mothers.